CH3NH3PbI3 perovskite single crystals: surface photophysics and their interaction with the environment. Issue 12 (2nd October 2015) - Grancini, G.; D'Innocenzo, V.; Dohner, E. R.; Martino, N.; Srimath Kandada, A. R.; Mosconi, E.; De Angelis, F.; Karunadasa, H. I.; Hoke, E. T.; Petrozza, A.
Abstract : Structural inhomogeneity on a micrometer-scale across a CH3 NH3 PbI3 single crystal is responsible for a local modulation of the optical band gap, which is also highly sensitive to humidity. Abstract : Here we identify structural inhomogeneity on a micrometer scale across the surface of a CH3 NH3 PbI3 perovskite single crystal. At the crystal edge a local distortion of the crystal lattice is responsible for a widening of the optical bandgap and faster photo-carrier recombination. These effects are inherently present at the edge of the crystal, and further enhanced upon water intercalation, as a preliminary step in the hydration of the perovskite material.